Young English language learners making thinking and language visible - Salmon, Angela K (Colombian Applied Linguistics Journal, 2008)
This paper aims to provide teachers with a resource to assist them in understanding the inner workings of young English Language Learners (ELLs) and how they externalize their thoughts in either their first or second language. This article not only analyzes how teachers can help children acquire a second language without sacrificing their first language and motivation, but also focuses on language processing in bilingual children through providing an understanding of both the interplay between language and cognition and the role of the environment. Results from an action research project implementing Harvard Project Zero’s Visible Thinking ideas serve as evidence to discuss the benefits of creating a culture of thinking in the classroom to promote additive bilingualism in young children.